Comparing Patterns in Antimicrobial Use During Global Point Prevalence Study at a Single Tertiary Hospital in Ghana: Implications for Antimicrobial Stewardship Programme - Enimil, Anthony; Agbedinu, Kwabena; Yeboah, Michael; Pauwels, Ines; Goossens, Herman; Ansong, Daniel; Mensah, Nicholas; Vesporten, Ann (Frontiers in Tropical Diseases, 2022)
Background: The Global Point Prevalence Study (PPS) provides a platform for institutions to register and add clinical information on antimicrobial usage and determine variables related to proper antimicrobial stewardship. Objective: To assess the trends in antimicrobial usage and quality indicators in antimicrobial prescriptions at our hospital. Method: We retrospectively compared data collected at Komfo Anokye Teaching Hospital (KATH) during the Global PPS in 2015 and 2019. Both surveys took place on a day in September of the respective year. Medical records of all in-patients on admission at 0800 hours on a specific day were reviewed for antimicrobial use in the survey. Data on antibiotic use, including indications for use and the presence of quality indicators, were recorded. Results: The total number of patients on admission in 2015 and 2019 were 386 and 630, respectively. The proportion of patients on at least one antimicrobial was 64% (247/386) and 58.4% (368/630) in 2015 and 2019, respectively. Pneumonia was the most common medical condition for which antimicrobial was prescribed for 2015, 30(16.9%) and 2019, 44(23.0%), respectively. There was a decrease in Hospital-acquired infections from 2015, 6.2% (24/386) to 4.8% (30/630) in 2019. The use of biomarkers increased from 4.9% (12/247) to 7.6% (28/368). Conclusion: Over 50% of hospitalised patients were on antimicrobials for both years. The inauguration of the antimicrobial stewardship committee at KATH will improve these quality indicators.